What determines the capital structure of farms? Empirical evidence from Poland - Geoffroy Enjolras; Gilles Sanfilippo; Michał Soliwoda (Baltic Journal of Economics, 2021)
The purpose of this paper is to analyse capital structure and its dynamics for farms in Poland, a leading European Union producer. The theoretical framework is based on the trade-off and pecking order theories of capital structure. We use data from the Farm Accountancy Data Network (FADN), which is representative of Polish professional farms during the period 2009-2018. We adopt a dynamic partial adjustment model using the generalized method of moments in order to explain the financing of farms through debt. The results show that Polish farms exhibit low target levels of debt, which they adjust dynamically, thus partially validating the trade-off theory. While size and growth opportunities positively influence the indebtedness of farms, profitability and land have the opposite effect. Polish farmers therefore use available internal funds, especially retained earnings, as a substitute for debt, in line with the pecking order theory.
Keywords: 330; Capital structure; farms; financing; Poland